Implementasi Ekonomi Syariah Tanpa Riba Sebagai Model Strategi Masyarakat Nagori Senio Membangun Kemandirian Finansial - Azizah Hanum; Windy Adinda Sari; Zahratun Aini; Devi Indriyani; Irfan Fauzan Marpaung (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to analyze the understanding, implementation, and strategies of the Nagori Senio community in applying the principles of interest-free (riba-free) Islamic economics as a foundation for strengthening financial independence. A community empowerment approach was employed through socialization, education, and collaboration with village authorities and Islamic financial institutions to enhance Islamic financial literacy and encourage changes in economic behavior. The results indicate that the community's understanding of riba, Islamic contracts (aqad), and muamalah principles is strongly influenced by access to education and experience in utilizing Islamic financial services. Continuous education has been proven to improve the community’s to distinguish between halal and non-halal transactions and promote prudence in selecting financing sources. The implementation of riba-free principles is reflected in the utilization of murabahah, mudharabah, musyarakah, and qardhul hasan contracts, providing fairer and more transparent financing alternatives for both the community and MSME actors. Islamic financial institutions play a crucial role in providing interest-free capital access and helping the community avoid dependency on high-interest loans. Strategies for financial independence are carried out through the enhancement of Islamic literacy, business mentoring, and the use of sustainable Islamic microfinance. These findings demonstrate that riba-free Islamic economics can serve as an effectivframework for strengthening local economic resilience and promoting the welfare development of rural communities.